Indigenous Languagages in Bangladesh: A Sociolinguistics Study - Awal, Abdul (Indonesian Journal of Integrated English Language Teaching, 2024)
The paper reveals the socio-linguistic position of Bangladesh where numerous indigenous or ethnic languages are under the threat of ‘Language Loss’. At present day language loss or language death has become a common phenomenon in different territories in the world, Bangladesh is in no difference. Extinction of indigenous languages in Bangladesh is associated with several socio-political and cultural reasons as well as the unconsciousness of language planning and policy making. It is noted that due to the domination of one variety of language over another language or another variety has made the threat of language loss. Our study explores the historical and political reasons of language loss, linguistic imperialism, and physiological state of indigenous speakers about their mother languages as well as national and international linguistics rights in this land. We know that language loss is vividly accompanied with the loss of cultural, aboriginal and racial heritage. The paper also accumulates the picture of language loss and threat of different indigenous communities with references. It is believed that the course of language extinction is executed by oppression and suppression as well as the trap of power politics. The papers inter-links between linguicism and language loss, which can be considered as a violation of Linguistic Human Rights of Bangladesh. The role of media and government are mentioned herewith with several propositions about how to reverse and cease loss of indigenous languages. The present situations of major indigenous languages and the linguistic inferiority complex are illustrated vividly in intra-national and international levels with due references.